2013
DOI: 10.1186/2050-6511-14-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and pharmacological evaluation of the nicotinic cholinergic system in chagasic rats

Abstract: BackgroundTwo theories attempt to explain the changes observed in the nicotinic acetylcholine receptors (nAChRs) in chagasic cardiomyopathy. The neurogenic theory proposes that receptor changes are due to loss of intracardiac ganglia parasympathetic neurons. The immunogenic theory proposes that the nAChRs changes are the result of autoantibodies against these receptors. Both theories agreed that nAChRs functional expression could be impaired in Chagas disease.MethodsWe evaluated nAChRs functional integrity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…The acute phase of the disease appears shortly after infection, and the chronic phase appears after a silent asymptomatic period that can last for several years. The heart, esophagus, colon and peripheral nervous system can be irreversibly damaged during the chronic phase of Chagas disease, and the majority of patients usually die from heart failure [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…The acute phase of the disease appears shortly after infection, and the chronic phase appears after a silent asymptomatic period that can last for several years. The heart, esophagus, colon and peripheral nervous system can be irreversibly damaged during the chronic phase of Chagas disease, and the majority of patients usually die from heart failure [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…In a different publication, we observed that rats with chronic Chagas disease had parasympathetic disturbances that could be the consequence of alterations on the muscarinic receptor distribution at different neural integration levels [15]. Recently we have also demonstrated a decrease in cardiac response to vagal stimulation in rats with chronic Chagas' disease, which was reverted by a pharmacological blockage of cholinesterase enzyme with neostigmine [16].…”
Section: Introductionmentioning
confidence: 83%
“…30 Indeed, it seems that dysautonomy in patients with Chagas heart disease is not only related to augmented sympathetic activity, but also to loss of parasympathetic modulation. 31 Accordingly, cholinergic function is impaired in chronic Chagas disease in rats, 32 an effect that may also be caused by autoimmunological mechanisms. 33 This complex pathophysiological milieu might, at least partially, explain the lack of response of our patients to renal denervation.…”
Section: Discussionmentioning
confidence: 99%